2008
DOI: 10.1143/jjap.47.2719
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Memory Using Epitaxially Grown Composite-Oxide-Film Technology

Abstract: We have developed a ferroelectric-gate field-effect transistor (FeFET) composed of heteroepitaxially stacked oxide materials. A semiconductor film of ZnO, a ferroelectric film of Pb(Zr,Ti)O 3 (PZT), and a bottom gate electrode of SrRuO 3 (SRO) are grown on a SrTiO 3 (STO) substrate. Structural characterization shows a heteroepitaxy of the fabricated ZnO/PZT/SRO/STO structure with good crystalline quality and the absence of an interface reaction layer. When the polarization direction of the PZT film is downward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 26 publications
4
59
0
Order By: Relevance
“…Figure 3(a) shows a SEM image of an area of a LSMO bilayer deposited over strontium titanate substrate using the spin coating technique. The LSMO bilayer shows good morphological characteristics that are comparable with those reported for films deposited using more sophisticated techniques, such as pulse laser deposition [18]. The analyzed film surface does not show a strong granular character, which indicates the formation of a dense surface.…”
Section: Resultssupporting
confidence: 72%
“…Figure 3(a) shows a SEM image of an area of a LSMO bilayer deposited over strontium titanate substrate using the spin coating technique. The LSMO bilayer shows good morphological characteristics that are comparable with those reported for films deposited using more sophisticated techniques, such as pulse laser deposition [18]. The analyzed film surface does not show a strong granular character, which indicates the formation of a dense surface.…”
Section: Resultssupporting
confidence: 72%
“…A highly orientated ferroelectric film and a clear interface are the key techniques to realize good electrical properties [29], [30]. Therefore, we used a Pt(111) film as the seed layer for the gate electrode to grow a well-oriented film on polycrystalline or amorphous substrates.…”
Section: Device Structure and Fabricationmentioning
confidence: 99%
“…Kato et al reported that a 2D electron gas is formed at the PZT/ZnO interface and can be controlled by the polarization direction of the PZT. [ 15 ] Yoon et al reported research on an organic ferroelectric thin-fi lm transistor using Al 2 O 3 as an insulating layer and ZnO as a channel layer. [ 16 ] 3.…”
Section: Introductionmentioning
confidence: 99%